O índio no discurso da imprensa escrita - del Vigna, Dalva (Cadernos de Linguagem e Sociedade, 2017)
Brazilian Indians have been coníronted with many different problems in the process of contact wilh the non-indigenous population. This paper presents a research of newspaper reports about lhe Indians. These reports show how language can be used to guide readers' view. Thus, language can, at times, be instrumental to ideology.